Influencia de los recursos didácticos elaborados con material no convencional en el desarrollo de habilidades motrices en octavo grado - Maldonado González, Adán Keyner; Tinoco Tinoco, Bryan Steeven (Machala: Universidad Técnica de Machala, 2023)
The main objective of this investigative work was oriented to promote the elaboration and practice of didactic resources with non-conventional material for the improvement of motor development in the eighth-year students of basic education of the Angel Tinoco Ruiz school. The data collection was based on the mixed approach with a descriptive methodology, managing to diagnose the reality in the Angel Tinoco Ruiz school in relation to the use of didactic resources made with non-conventional material to develop motor skills in students, regarding the The same objective was aimed at promoting the use of didactic resources with non-conventional material for the improvement of the development of motor skills. The methods with the highest incidence in this investigation are the analytical-synthetic and others that were integrated as auxiliaries, such as, the comparative and the bibliographic, which contributed significantly when collecting the information based on the specific objectives to contribute to the study. general objective, which were written to cover aspects related to literary review, field research and finally to support the integrative proposal, as a contribution in favor of the educational institution that facilitated access to carry out the research. In relation to the sample, the Physical Education teacher of the upper basic sublevel was considered, in addition, the eighth year students of basic education of the aforementioned school were taken into account. The selected instruments were, interview applied to the teacher and the student survey, which for its construction related the objects of study, from which three dimensions were derived and consequently the indicators served as a guide for the elaboration of the instruments with a scale of Likert, which facilitated the reception of opinions and attitudes of the people involved in this investigative work and at the same time scoring from fixed responses the range of values. The analysis of the results in the survey shows that the Physical Education teacher does not elaborate or use didactic resources with non-conventional material that contributes to the development of motor skills. Based on the foregoing and responding to the third specific objective, the integrative proposal was defined, which was oriented to determine the experience that the teacher has for the elaboration and use of didactic resources with non-conventional material in the motor development of the students as a contribution for the improvement of the teacher's competences on the elaboration and use of didactic resources with recycled material. The proposal consisted of three implementation phases aimed at, preparing the methodological guide, socializing it with the teacher and rector, and evaluating its feasibility, In addition, the logistical resources and the feasibility assessment were included with the dimensions, technical, economic, social and environmental, demonstrating the ability to achieve the objectives of the proposal, determining the feasibility and material capacities of the executing parties of the project. proposal. Finally, the conclusions, recommendations, limitations and prospective of the research carried out were established.
El objetivo principal de este trabajo investigativo se orientó en impulsar la elaboración y práctica de recursos didácticos con material no convencional para el mejoramiento del desarrollo motriz en los estudiantes de octavo año de educación básica del colegio Ángel Tinoco Ruiz. La recopilación de datos se fundamentó desde el enfoque mixto con una metodología de carácter descriptivo, logrando diagnosticar la realidad en el colegio Ángel Tinoco Ruiz en relación con el uso de recursos didácticos elaborados con material no convencional para desarrollar habilidades motrices en los estudiantes, respecto al objetivo el mismo que estuvo dirigido a impulsar el uso de recursos didácticos con material no convencional para el mejoramiento del desarrollo de las habilidades motoras. Los métodos de mayor incidencia en esta indagación es el analítico-sintético y otros que se integraron en calidad de auxiliares, como, el comparativo y el bibliográfico, mismos que aportaron significativamente al momento de recabar la información con base a los objetivos específicos para contribuir al objetivo general, mismos que estuvieron redactados para abarcar aspectos relacionados con la revisión literaria, con la investigación de campo y finalmente para sostener la propuesta integradora, como aporte a favor de la institución educativa que facilitó el acceso para concretar la investigación. En relación con la muestra se consideró al docente de Educación Física del subnivel de básica superior, además, se tomó en cuenta a los estudiantes de octavo año de educación básica del mencionado colegio. Los instrumentos seleccionados fueron, entrevista aplicada a la docente y la encuesta a los estudiantes, que para su construcción se relacionó los objetos de estudio, de donde se derivaron tres dimensiones y en consecuencia los indicadores sirvieron de guía para la elaboración de los instrumentos con una escala de Likert, que facilitó la recepción de opiniones y actitudes de las personas vinculadas en este trabajo investigativo y al mismo tiempo puntuar a partir de respuestas fijas el rango de valores. El análisis de resultados en la encuesta se demuestra que la docente de Educación Física no elabora ni utiliza recursos didácticos con material no convencional que contribuya al desarrollo de las habilidades motrices. Por lo que antecede y respondiendo al tercer objetivo específico, se definió la propuesta integradora que se orientó a determinar la experiencia que tiene la docente para la elaboración y uso de recursos didácticos con material no convencional en el desarrollo motriz de los estudiantes como aporte para el mejoramiento de las competencias del docente sobre elaboración y uso de recursos didácticos con material reciclado. La propuesta estuvo compuesta de tres fases de implementación dirigidas a, elaborar la guía metodológica, socializarla con la docente, rectora y evaluar la factibilidad de la misma, además se incluyó los recursos logísticos y la valoración de la factibilidad con las dimensiones, técnica, económica, social y ambiental, demostrando la capacidad para lograr los objetivos de la propuesta, determinando la viabilidad y capacidades materiales con los que cuentan las partes ejecutaros de la propuesta. Finalmente se establecieron las conclusiones, recomendaciones, limitaciones y prospectiva de la investigación realizada.
Keywords: ELABORACION; RECURSO DIDACTICO; MOTRICIDAD; MATERIAL NO CONVENCIONAL